Tourism and Its Prospects in Giridih, Jharkhand - Archana Sada Suman Tudu, R K; Sarma, Rabindranath (International Journal of Psychosocial Rehabilitation, 2020)
Giridih is one district among the 24 of the Jharkhand state. It is situated between the districts of Jamtara, Bokaro, Koderma, Hazariabgh, and Dhanbad. Initially, it was part of Hazaribagh district. It was formed on 6th December 1972.The state of Jharkhand has enormous tourism potential. This study aims to explore the perspectives surrounding tourism and its potential in Jharkhand’s Giridih district. Parasnath is a pilgrimage site that attracts people from all over the world, and Khandoli Dam and Usri Falls are the other appealing tourist spots situated in the district. Through this paper, the researcher has tried to provide some informative insights and exposures on the subject.